The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/nph.17375
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal thaw and landscape position determine foliar functional traits and whole‐plant water use in tall shrubs on the low arctic tundra

Abstract: Climate warming is driving tundra shrub expansion with implications for ecosystem function and regional climate. Understanding associations between shrub ecophysiological function, distribution and environment is necessary for predicting consequences of expansion. We evaluated the role of topographic gradients on upland shrub productivity to understand potential constraints on shrub expansion.At a low arctic tundra site near Inuvik, Northwest Territories, Canada, we measured sap flow, stem water potential and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…Topographic position is generally a strong predictor of tundra plant function and community composition, due to the downslope movement of water and nutrients (Walker, 2000). There is little evidence of a strong topographic nutrient or moisture gradient at our study site however, though snow depth has been found to increase downslope (Black et al, 2021; Wallace & Baltzer, 2020). For this reason, we also hypothesized that topographic control on snow depth may constrain alder height however, as mentioned previously, the relationship between snow depth and height was weaker than expected (Figure 1).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Topographic position is generally a strong predictor of tundra plant function and community composition, due to the downslope movement of water and nutrients (Walker, 2000). There is little evidence of a strong topographic nutrient or moisture gradient at our study site however, though snow depth has been found to increase downslope (Black et al, 2021; Wallace & Baltzer, 2020). For this reason, we also hypothesized that topographic control on snow depth may constrain alder height however, as mentioned previously, the relationship between snow depth and height was weaker than expected (Figure 1).…”
Section: Discussionmentioning
confidence: 60%
“…The decrease in the number of mature alder individuals near patch bottoms is surprising, given the general trends of increased shrub expansion at the base of slopes and valley bottoms (Naito & Cairns, 2011; Tape et al, 2006). This divergence may be due to the limited topographic moisture or nutrient gradients previously observed at our study site (Black et al, 2021; Wallace & Baltzer, 2020). Instead, the decreasing trend may be a response to increased competition with taller shrubs at slope bottoms as alder in Alaska has been shown to respond strongly to intraspecific competition (Chapin et al, 1989); however, confirmation of this requires further study of this mechanism in our study region.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…5.6b). Shrubs growing on elevated sites have previously been found to show lower temperature response or productivity due to higher drainage and drier conditions (Ackerman et al 2017, Black et al 2021. However, drier conditions on the Yedoma Ridge are not evident from available field measurements (table 5.…”
Section: Spatiotemporal Contrasts In Response To Summer Conditionsmentioning
confidence: 99%
“…The influence of climate factors on growth of Arctic shrubs is unlikely to be spatially and temporally uniform. Contrasts in climate response across topographical and hydrological gradients are increasingly emerging from dendrochronological and monitoring studies (Opała-Owczarek et al 2018, Black et al 2021, Dobbert et al 2021), both on coarser, panarctic scale with longer records (Buchwal et al 2020), regional scale (Ropars et al 2015, Ackerman et al 2017) and highly local (sub-kilometer) scales (Black et al 2021, Dobbert et al 2021. Contrasts in moisture availability have been related to differences in shrub temperature response on panarctic (Buchwal et al 2020) to regional scale (Ropars et al 2015, Ackerman et al 2017, and additional microscale variability in shrub growth has been observed under differential snow accumulation (Lawrence and Swenson 2011, Loranty and Goetz 2012, Krab et al 2018, Wilcox et al 2019, Dobbert et al 2021.…”
Section: Introductionmentioning
confidence: 99%